Validation of the albumin–indocyanine green evaluation model in patients with resected hepatocellular carcinoma and comparison with the albumin–bilirubin score. (16th January 2019) - Russolillo, Nadia; Forchino, Fabio; Conci, Simone; Mele, Caterina; Langella, Serena; Ruzzenente, Andrea; Scoleri, Iolanda; Giuliante, Felice; Guglielmi, Alfredo; Ferrero, Alessandro
Abstract: Background: The albumin–indocyanine green evaluation (ALICE) model based on serum albumin and indocyanine retention rate has been shown to be an effective method for predicting postoperative outcomes in hepatocellular carcinoma patients. Aim of the study was to validate the ALICE model in a large Western cohort of patients by comparing the albumin–bilirubin (ALBI) score and Child–Turcotte–Pugh (CTP) score. Methods: A total of 400 patients who underwent hepatic resection from January 2005 to June 2016 at three centers were enrolled. The ALICE, ALBI, and CTP scores were computed for all patients. Results: The ALICE score correlated better with ALBI ( r = 0.428) than with CTP score ( r = 0.302). Both the ALICE (grade 1: 49%; grade 2: 51%) and the ALBI (grade 1: 52.5%; grade 2: 47.5%) scores stratified the CTP class A patients into two distinct classes. The incidence of ascites (grades 1–3: ALICE 11%, 20%, 58%; ALBI 11%, 23%, 50%) and severe liver failure (ALICE 8.7%, 10.5%, 41.7%; ALBI 8.6%, 12%, 50%) increased with increasing ALBI and ALICE grade and were similar for the same grade. Conclusions: The ALICE model can assess hepatic functional reserve and predict postoperative outcomes with efficacy comparable with the ALBI grade and better than the CTP score. Abstract : Highlight Russolillo and colleagues validated the usefulness of the ALICE model, based on the serum albumin and indocyanine green retention rate, in predicting postoperative outcomes after resection for HCC. The efficacy of the ALICE model was comparable with that of the albumin‐bilirubin grade and better than that of the Child‐Turcotte‐Pugh score.